The relationship between ward head leadership style and nurse performance in inpatient care at Nahdlatul Ulama Hospital in Jombang - Moh. Choirul Anam; Ahmad Nur Khoiri (Journal of Clinical Nursing Studies and Practice, 2026)
Insufficient motivation and supervisory support, together with an unfavorable organizational climate, may adversely affect nurses' performance. Leadership style is a central component of nursing management because it directly influences service quality and staff productivity. The head nurse therefore plays an important role in shaping nurses' performance in patient care. This study aimed to examine the relationship between head nurses' leadership styles and nurses' performance in the inpatient units of Nahdlatul Ulama Hospital, Jombang. An analytic correlational design with a cross-sectional approach was employed. A total of 47 respondents were selected from a population of 53 using purposive sampling. Data were collected using a leadership-style questionnaire and a nurse performance assessment form and analyzed using the Chi-square test at a significance level of 0.05. The findings showed that the majority of head nurses applied a democratic leadership style (66.0%), while almost all nurses demonstrated fairly good performance (89.4%). The statistical analysis yielded a value of rho = 0.000 (rho < 0.05), indicating a statistically significant and strong relationship between head nurses' leadership styles and nurses' performance. A leadership approach that is appropriately aligned with staff characteristics can positively influence nurses' performance in delivering patient care. Accordingly, the leadership style adopted by head nurses is an important determinant of improved nurse performance.